2017
DOI: 10.11607/jomi.4975
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Nanotube Surface–Treated Dental Implants Loaded with Doxycycline on Growth Reduction of Porphyromonas gingivalis

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Moreover, dental implants formed of titanium nanotube surface coated with polylactic-co-glycolic acid and doxycycline have shown to provide pH-sensitive systems for a controlled release of the drug [202]. Porphyromonas gingivalis growth has been demonstrated to be inhibited, during a 28 day period interval, by nanotubes loaded with doxycycline on the dental implant surface [203]. In addition, doxycycline-based coatings were found to prevent microorganism colonization and consequently control of peri-implant mucositis and peri-implantitis [204].…”
Section: Drug-releasing Coatingsmentioning
confidence: 99%
“…Moreover, dental implants formed of titanium nanotube surface coated with polylactic-co-glycolic acid and doxycycline have shown to provide pH-sensitive systems for a controlled release of the drug [202]. Porphyromonas gingivalis growth has been demonstrated to be inhibited, during a 28 day period interval, by nanotubes loaded with doxycycline on the dental implant surface [203]. In addition, doxycycline-based coatings were found to prevent microorganism colonization and consequently control of peri-implant mucositis and peri-implantitis [204].…”
Section: Drug-releasing Coatingsmentioning
confidence: 99%
“…[78][79][80] The TiO 2 nanotubular structure is able to load biofunctionalizing molecules to enhance the hard tissue integration and to deliver drugs for local therapeutic effects. [81][82][83][84][85] In fact, this implant surface modification has been evaluated for osteogenic potential with combination of bioactive molecules including growth factors. 82,86,87 The feature of drug release from TiO 2 nanotubes has been utilized for local therapies, which are mainly osteogenic effects in compromised bone conditions like osteoporosis and antibacterial effects.…”
Section: Nanoscale Surface Modifications Anodic Oxidation Of Timentioning
confidence: 99%
“…82,86,87 The feature of drug release from TiO 2 nanotubes has been utilized for local therapies, which are mainly osteogenic effects in compromised bone conditions like osteoporosis and antibacterial effects. 79,81,[88][89][90] The drug release has been found to be effective when the diameter of TiO 2 nanotubes is larger than approximately 100 nm, which is slightly different from the optimal diameter for osteogenesis. 90,91 TiO 2 nanotubular topography has antibacterial properties with carriage of antibiotic drugs or metal doping.…”
Section: Nanoscale Surface Modifications Anodic Oxidation Of Timentioning
confidence: 99%
“…Vancomycin was covalently attached to the implant surface to make an antibacterial surface to prevent the bacteria attachment for a long time [240]. Ferreira et al incorporated nanotubes loaded with doxycycline on the dental implant surface to deliver the antibiotic locally and reported that P. gingivalis growth was suppressed in the experimental media during a 28 day time interval [214]. Likewise, it was reported recently that an implant surface coated with doxycycline prevented bacterial colonization to control peri-implant mucositis and peri-implantitis [213].…”
Section: Antibacterial Coatingsmentioning
confidence: 99%